A minimum gradient algorithm for phased-array null formation - Kogan, Leonid (Radio science, 2005)
Formation of the null at the phased‐array beam pattern pointed toward the source of a radio frequency interference (RFI) can serve to mitigate the effects of that RFI. Several algorithms for creating a null at the phased‐array beam pattern have been designed. On the basis of an array side lobe minimization algorithm (Kogan, 2000), a new method for creating a null at the phased‐array beam pattern is described here. The algorithm is a straightforward one and can have an advantage in creating wide‐area nulls, especially for phased arrays with a small number of antennas. We have tested this algorithm for a possible Square Kilometre Array antenna station configured as a phased array of 19 antennas and for the Very Large Array configuration D (VLA‐D), working as a phased array for very long baseline interferometry experiments. The null is created at the given area around the given direction. The narrow null (∼0.1 ) deeper than 100 dB level can be achieved at the cost of a 2% decrease in the signal‐to‐noise ratio in the main direction. The creation of such a deep null can be impractical for many reasons, however, first and foremost because the phases and weights would have to be specified with impractical precision. Rounding the phase and weights to 1° and 0.01, respectively raises the null up to ∼50 dB.